2015
DOI: 10.1007/s10534-015-9859-3
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein, essential elements and lipid peroxidation in mercury-exposed suckling rats pretreated with selenium

Abstract: Detoxification of mercury (Hg) with selenium (Se) in the early postnatal period with regard to the expression of metallothionein protein (MT), essential element status, and lipid peroxidation level in tissues has not been studied. Seven-day-old Wistar pups were orally pretreated with Se [6 μmol Na2SeO3/kg body weight (b.w.)] for 3 days and then cotreated with Hg (6 μmol HgCl2/kg b.w.) for the following 4 days. This group (Se + Hg) was compared to the groups treated with Hg, Se, or vehicle (control). Compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Selenium is considered to be an antidote in the treatment of mercury intoxication [ 158 ], it may modulate Hg toxicity through the influence on Hg deposition in tissues, as well as Hg-induced oxidative stress, inflammation, excitotoxicity, and other pathways [ 127 ]. Studies by Orct et al [ 135 ] demonstrated the protective effect of selenium on oxidative lipid damage in the brain, which is extremely sensitive to mercury during the early postnatal period. Severe selenium deficiency causes irreversible brain injury [ 159 ].…”
Section: Biochemistry Of Seleniummentioning
confidence: 99%
See 1 more Smart Citation
“…Selenium is considered to be an antidote in the treatment of mercury intoxication [ 158 ], it may modulate Hg toxicity through the influence on Hg deposition in tissues, as well as Hg-induced oxidative stress, inflammation, excitotoxicity, and other pathways [ 127 ]. Studies by Orct et al [ 135 ] demonstrated the protective effect of selenium on oxidative lipid damage in the brain, which is extremely sensitive to mercury during the early postnatal period. Severe selenium deficiency causes irreversible brain injury [ 159 ].…”
Section: Biochemistry Of Seleniummentioning
confidence: 99%
“… Physiological effects of selenium. Selenium is known for its antioxidant, antimutagenic and anticarcinogenic properties, it also acts against microbes as well as parasites and has antiinflammatory effects, engages in metabolism, growth and development, protects organs from oxidative stress, affects immune function and improves fertility [ 2 , 47 , 48 , 49 , 50 , 53 , 54 , 60 , 82 , 87 , 104 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ]. …”
Section: Figurementioning
confidence: 99%
“…It is well known that MT chelates various metals (e.g., cadmium, copper, zinc, mercury and silver) (Carpenè et al ., ; Figueira et al ., ; Mulley et al ., ; Orct et al ., ). In the present study, the mRNA levels of MT1 and MT2 were significantly increased by Ag + 4 h after exposure, then decreased as the exposure time increased (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…In terrestrial mammals, such as rats and mice, binding of Hg to MT has been demonstrated and induction of these proteins after Hg exposure (Morcillo and Santamaria, 1993;García-Sevillano et al, 2015;Orct et al, 2015). However, the role of MT in the detoxification of Hg is controversial; studies in marine mammals have indicated that a small percentage of Hg is bound to MT in liver and kidney (Decataldo et al, 2004;Ikemoto et al, 2004aIkemoto et al, , 2004b.…”
mentioning
confidence: 99%